2005
DOI: 10.1016/j.cub.2005.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar Complex Spike Firing Is Suitable to Induce as Well as to Stabilize Motor Learning

Abstract: We suggest that CS firing may underlie the stabilization of a learned motor behavior, rather than serving as an electrophysiological correlate of an error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
110
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(118 citation statements)
references
References 25 publications
7
110
0
1
Order By: Relevance
“…Such well directed changes in effectiveness could be a consequence of the modulation of the climbing fibers responses. In fact, we have recently shown (20) that STSA leads to a redistribution of CSs with more CSs right around saccade end in the case of inward adaptation and a CS pause around the time of saccade end in the case of outward adaptation. Assuming that CSs induce long-term depression of parallel fiber synapses (21), more CSs around the saccade end should suppress SS activity in this period, thereby shortening the PB as observed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Such well directed changes in effectiveness could be a consequence of the modulation of the climbing fibers responses. In fact, we have recently shown (20) that STSA leads to a redistribution of CSs with more CSs right around saccade end in the case of inward adaptation and a CS pause around the time of saccade end in the case of outward adaptation. Assuming that CSs induce long-term depression of parallel fiber synapses (21), more CSs around the saccade end should suppress SS activity in this period, thereby shortening the PB as observed.…”
Section: Discussionmentioning
confidence: 95%
“…The arrow indicates the course of adaptation. The CS responses were taken from a recent study on the influence of STSA on CS discharge patterns (20).…”
mentioning
confidence: 99%
“…We surmised that P-cells that already had SS activity related to saccades would be more likely to exhibit changes in CS activity during saccade errors than those that did not. Note that Catz et al (2005) tested all P-cells in folia with oculomotor activity whether or not the P-cells exhibited a saccade-related change in SS activity. To test for saccade-related SS activity, we asked the monkey to make 15°saccades to target jumps that started straight ahead and landed along one of eight directions spaced at 45°intervals from 0 to 315°and chosen pseudo-randomly (Spike2 random number generator function).…”
Section: General Proceduresmentioning
confidence: 99%
“…During backward adaptation, Catz et al (2005) reported an increase in both the rate and duration of the average population CS response as adaptation evolved. The change began during the saccade and ended early in the intersaccadic error interval (their Fig.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…The deeper layers of the SC are connected to the medioposterior cerebellum (caudal fastigial nucleus and oculomotor vermis; Ohtsuka and Noda 1990) via nucleus reticularis tegmenti pontis (NRTP; May et al 1990;Ohtsuka and Noda 1990) and dorsal lateral pontine nucleus (Thier and Mock 2005). Lesions to the medioposterior cerebellum impair rapid saccade amplitude adaptation during the McLaughlin task (Barash et al 1999;Robinson et al 2002;Takagi et al 2000) and the burst metrics of neurons in NRTP (Takeichi et al 2005), caudal fastigial nucleus (Inaba et al 2003;Scudder and McGee 2003), and oculomotor vermis (Catz et al 2005(Catz et al , 2008Soetedjo and Fuchs 2006) are altered along with saccade amplitude during head-restrained saccadic adaptation. Future studies are required to classify the types of motor command signals (gaze, eye, or head) represented at each level of this circuit prior to describing modifications to these signals during gaze adaptation using the McLaughlin task.…”
Section: Physiological Implicationsmentioning
confidence: 99%